Integrasi Proyek dan Asesmen dalam Pembelajaran Matematika: Studi Literatur tentang Paradigma Baru Evaluasi Autentik - Baharuddin (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
The transformation of 21st-century education demands a fundamental shift in the paradigm of mathematics learning, from one that initially focused on mastering abstract concepts to one that is more meaningful, contextual, and oriented towards developing students' authentic competencies. This study aims to examine in depth the integration of projects and assessments in mathematics learning as an effort to build a new paradigm of authentic evaluation that is in line with the demands of modern education. The method used is a systematic literature review of various previous studies discussing the implementation of authentic assessment and project-based learning, especially in the context of mathematics education. The results of the review indicate that most studies still position projects and assessments as two separate components, rather than as a mutually supportive unit within a complete learning framework. This study reveals conceptual and practical gaps in the integration of these two approaches, particularly regarding the design of evaluation instruments that can assess both the process and learning outcomes holistically. Thus, this study offers a conceptual synthesis that the integration of projects and authentic assessments can become a new paradigm of evaluation in mathematics learning, which not only assesses cognitive abilities but also develops students' creativity, collaboration, reflection, and higher-order thinking skills. The implications of this study are expected to strengthen the theoretical foundation and provide direction for the development of assessment models that are contextual, adaptive, and aligned with the Independent Learning policy and the needs of 21st-century learning.